PAPR reduction in wavelet packet-based OFDM using PSO-based PTS technique. (2017) - Singh, Pushpinder; Pal, Saloni; Sood, Neetu
In multicarrier modulation scheme, PAPR reduction is the main problem. Techniques mentioned in literature are either too complex or not optimal. In this paper, an attempt has been made to reduce the PAPR of multi carrier modulation with the much less complexity. Wavelet packet-based orthogonal frequency division multiplexing has been employed with orthogonal subcarriers and similarly to OFDM high spectral efficiency is achieved in WP-OFDM by the overlapping subcarriers spectra. Further, PSO-based PTS techniques have been used to reduce the PAPR with much less complexity as compared to conventional optimal PTS technique in which search complexity increases exponentially. The performance of WP-OFDM for PTS technique and PSO-based PTS techniques have been implemented in this paper. Also, the simulation results are obtained shows that the PAPR is reduced significantly with much less search complexity.